Consumption and communication perspectives of IT in a developing economy. Issue 8 (3rd August 2019) - Ozuem, Wilson; Howell, Kerry E.; Lancaster, Geoff
ABSTRACT: Technological innovations are important sources of competitive advantage when there is a balanced rate of adoption that helps organisations maintain or improve performance levels. This paper synthesises and builds on efforts to conceptualise the adoption and implementation of technologically induced customer services in developing countries. Its point of departure is recent advances in computer-mediated marketing environments (CMMEs). It assesses relationships between customer services and evolving technologies in the provision of services in the banking sector. Using phenomenological hermeneutics and a case study approach, we iteratively engaged with data that emerged to identify core values and community-based values. These facets were further developed into seven main issues (core values: quality, education and reach, and community-based values: efficiency, usability, control and security). The paper offers practical steps by which companies and institutions may counter these issues and the theoretical implications for wider considerations are discussed.